The Suez Canal: Past Lessons and Future Challenges
XXXI, 264 p. 31 illus., 29 illus. in color.
Keywords: “This book should be at the top of all reading lists as maritime commerce, global supply chains, and the Suez Canal will continue to profoundly affect our daily lives.” —Admiral Gary Roughead, U.S. Navy (Retired), Former U.S. Navy Chief of Naval Operations “The authors have filled a gap in the academic literature with this superb edited volume. Maritime trade is changing, the importance of sea resources is growing, and power rivalries are increasingly being expressed at sea.” —Bruno Tertrais, Deputy Director, Fondation pour la recherche stratégique, France This open access book provides an interdisciplinary analysis of the Suez Canal after 150 years of operation, studying it from various perspectives: political and geopolitical, energy, legal, and environmental and human impact. The book addresses several gaps in the scholarly literature, including a much-needed geostrategic analysis of the Canal in thevolatile Middle East amid structural changes in the international system, and topics that are usually less emphasized in the context of the Suez Canal, such as anthropogenic activity. Carmela Lutmar is Senior Lecturer in the Division of International Relations in the School of Political Sciences at the University of Haifa, Israel, and Adjunct Lecturer at New York University, USA. Ziv Rubinovitz is Research Fellow and Academic Coordinator at the Chaikin Chair for Geostrategy, Research Coordinator of the Maritime Policy and Strategy Research Center, the Ezri Center for Iran and Gulf States Research, and the Wydra Division of Shipping and Ports at the University of Haifa, Israel.